Bad Worlds. (17th June 2015) - Girard, Patrick; Weber, Zach
<x xml:space="preserve">Abstract</x> The idea of relevant logic—that irrelevant inferences are invalid—is appealing. But the standard semantics for relevant logics involve baroque metaphysics: a three‐place accessibility relation, a star operator, and 'bad' (impossible/non‐normal) worlds. In this article we propose that these oddities express a mismatch between non‐classical object theory and classical metatheory. A uniformly relevant semantics for relevant logic is a better fit.